Integrated Deterrence and Strategic Stability in South Asia - Syeda Tahreem Bukhari; Abdul Basit; Nazia Sheikh (ASIAN Journal of International Peace & Security (AJIPS), 2023)
The 21st century witnesses a significant shift in global power dynamics, with the AsiaPacific region emerging as a crucial arena for determining the trajectory of global power transitions. The United States finds itself grappling with the ascendancy of China, prompting the adoption of an integrated deterrence approach. This strategy revolves around bolstering key allies, leveraging their capabilities to counter competitors, notably China. In this context, the strategic alignment between the United States and India within the framework of integrated deterrence raises concerns among other regional states particularly, Pakistan and China. The collaborative efforts to strengthen India’s role could potentially elevate India’s posture, thereby unsettling the strategic equilibrium and leading to strategic miscalculations. This article critically examines how India is going to benefit under the integrated deterrence approach and the implications of the US integrated deterrence approach in the South Asian region through the theoretical lens of Strategic Stability. This study aims to delve into the intricate interplay between the US integrated deterrence strategy and its ramifications for the fragile security situation in South Asia. The qualitative method has been applied in the research relying mainly on the secondary data.